Synthesis of Nitrogen-Containing Chalcone Via One-Pot Three-Component Reaction . part ii - Abualreish, Mustafa; Ljaleel, Anwar E. M. Nor E.; Fadul, Himat M. A.; Ayuob, Saad M. H.; Abdel Karim, M.; Van Der Westhuizen, Jan H. Van Der Westhuizen (International Journal of Advanced Chemistry, 2014)
The compound 3-Hydroxy-4'-methoxychalcone (1) was prepared by reacting 3-hydroxybenzaldehyde with 4-methoxyacetophenone.The aminomethylation of this chalcone was accomplished by reaction with formaldehyde and N-methylpiperazine in dry acetonitrile to Obtain 3-hydroxy-4'-methoxy-4-(N-methyl-piperazinomethyl) chalcone (2) and 3-hydroxy-4'-methoxy-2,4-bis-(N-methylpiperazinomethyl)chalcone(3). The products were purified by column and thin layer chromatography and were identified along with their intermediates by spectroscopic methods: UV, IR, NMR and mass spectrometry.